Loss of Partitioning-Defective-3/Isotype-Specific Interacting Protein (Par-3/ASIP) in the Elongating Spermatid of RA175 (IGSF4A/SynCAM)-Deficient Mice - Fujita, Eriko (American Society for Investigative Pathology, 2007)
IGSF4a/RA175/SynCAM (RA175) and junctional adhesion molecules (Jams) are members of the immunoglobulin superfamily with a PDZ-binding domain at their C termini. Deficiency of Ra175 (Ra175(−/−)) as well as Jam-C deficiency (Jam-C(−/−)) causes the defect of the spermatid differentiation, oligo-astheno-teratozoospermia. Ra175(−/−) elongating spermatids fail to mature further, whereas Jam-C(−/−) round spermatids lose cell polarity, and most of Jam-C(−/−) elongated spermatids are completely lost. RA175 and Jam-C seem to have similar but distinct functional roles during spermatid differentiation. Here we show that the cell polarity protein Par-3 with PDZ domains, a binding partner of Jams, is one of the associated proteins of the cytoplasmic region of RA175 in testis. Par-3 and Jam-C are partly co-localized with RA175 in the elongating and elongated spermatids; their distributions overlapped with that of RA175 on the tips of the dorsal region of the head of the elongating spermatid (steps 9 to 12) in the wild type. In the Ra175(−/−) elongating spermatid, Par-3 was absent, and Jam-C was absent or abnormally localized. The RA175 formed a ternary complex with Jam-C via interaction with Par-3. The lack of the ternary complex in the Ra175(−/−) elongating spermatid may cause the defect of the specialized adhesion structures, resulting in the oligo-astheno-teratozoospermia.